2016
DOI: 10.1370/afm.1993
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of Atypical Pathogens in Patients With Cough and Community-Acquired Pneumonia: A Meta-Analysis

Abstract: PURPOSE Community-acquired pneumonia (CAP), acute cough, bronchitis, and lower respiratory tract infections (LRTI) are often caused by infections with viruses or Streptococcus pneumoniae. The prevalence of atypical pathogens Mycoplasma pneumoniae, Chlamydophila pneumoniae, Legionella pneumophila, and Bordetella pertussis among patients with these illnesses in the ambulatory setting has not been previously summarized. We set out to derive prevalence information from the existing literature. METHODSWe performed … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
66
2
9

Year Published

2017
2017
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 78 publications
(78 citation statements)
references
References 79 publications
1
66
2
9
Order By: Relevance
“…The qRT-PCR was shown as the best way to detect an EV or PeV, but still little is known about the prognosis of these viruses. 34,35 In the present study, it was of significance to describe the circulation of EV 37 In addition, S. pneumoniae could be found to colonize the nasopharynx during RSV A/B infection in young children, which was associated with increased severity. 38 In accordance, 82.6% of S. pneumoniae infections were coinfected with a respiratory virus in which RSV A/B was the most identified pathogen.…”
Section: Children With Rv and Rsvmentioning
confidence: 72%
“…The qRT-PCR was shown as the best way to detect an EV or PeV, but still little is known about the prognosis of these viruses. 34,35 In the present study, it was of significance to describe the circulation of EV 37 In addition, S. pneumoniae could be found to colonize the nasopharynx during RSV A/B infection in young children, which was associated with increased severity. 38 In accordance, 82.6% of S. pneumoniae infections were coinfected with a respiratory virus in which RSV A/B was the most identified pathogen.…”
Section: Children With Rv and Rsvmentioning
confidence: 72%
“…The reported frequency of community-acquired pneumonia due to MP in pediatric patients worldwide varies from 1.5% to 17.6%. [21][22][23] Studies conducted in Latin America report frequencies ranging from 0.74% to 43.8%. [24][25][26] Most of the reports are from a previously healthy pediatric population.…”
Section: Discussionmentioning
confidence: 99%
“…1 A recent systematic review of the prevalence of BP infection in patients with prolonged cough found that the overall prevalence of BP infection among primary care patients with prolonged cough (typically Ͼ1 week) was 12.4%; it was 18% in studies of children-much higher than suggested by laboratory-based surveillance reports. 2 The recent large increase in pertussis cases in the United States has been described by the Centers for Disease Control and Prevention (CDC) as an epidemic. 3 For infants and young children, complications from pertussis may be life-threatening, and hospitalization may be warranted.…”
mentioning
confidence: 99%